DESAIN BIOFLOKULAN GELATIN TULANG IKAN LELE (CLARIAS BATRACHUS) UNTUK PENJERNIHAN AIR - Muhammad Alqodri; Muhammad Romli; Suprihatin Suprihatin (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
Coagulation-flocculation wastewater treatment is widely used because the process is simple to facilitate the sedimentation process. The coagulation-flocculation process aims to alter very small colloidal particles (smaller than 10-3) into larger particles using synthetic or natural materials. The synthetic material is preferred because it does not need to adjust the pH of the media; only small quantities required (from 1-5 ppm), the floc formed is larger, stronger, and has better settling properties. However, it has many shortcomings, including nonbiodegradable, neurotoxic, and carcinogenic properties. Gelatin can be used as an alternative bioflocculant because it has a dual function in the coagulation and flocculation processes. The gelatin production is obtained by utilizing the bone waste of catfish (Clarias batrachus) using the acid method. This study aimed to design gelatin flocculant from catfish bone waste by specifying the intended characteristics such as pH, molecular weight (Mv), non-toxic, and insoluble in neutral pH and determining the effectiveness in purifying water. The method coveredthe production of gelatin using the acid method, determining the properties of gelatin flocculants, performing test of the effectiveness for water purification using the jar test, and calculate the cost. The results showed that gelatin flocculant met the criteria for flocculants with a pH of 5.2, Mv value of 302.648 g/mol, and non-toxic insoluble in neutral pH. The jar test results showed that the administration of a gelatin flocculant dose of 40 mg/L at pH 5.5 was able to reduce the turbidity of the artificial waste from 100 NTU to 28 NTU with a turbidity removal value of 72% with estimated cost of treatment of Rp 4,000 /m3.Keywords: catfish bone waste, flocculation, gelatin flocculant, jar test, molecular weight